Thesaurus maintenance, alignment and publication as linked data: the AGROVOC use case. (14th August 2012) - Caracciolo, Caterina; Stellato, Armando; Rajbahndari, Sachit; Morshed, Ahsan; Johannsen, Gudrun; Jaques, Yves; Keizer, Johannes
The AGROVOC multilingual thesaurus maintained by the Food and Agriculture Organisation (FAO) of the United Nations is now published as linked data. In order to reach this goal AGROVOC was expressed in Simple Knowledge Organisation System (SKOS) and its concepts provided with dereferenceable URIs. AGROVOC is now aligned with ten other multilingual Knowledge Organisation Systems (KOS) related to agriculture, using the SKOS properties exact match and close match. Alignments were automatically produced in Eclipse using a customdesigned tool and then validated by a domain expert. The resulting data is publicly available to both humans and machines using a SPARQL endpoint together with a modified version of Pubby, a lightweight front-end tool for publishing linked data. This paper describes the process that led to the current linked data AGROVOC and discusses current and future applications and directions. This paper extends a shorter version presented at MTSR 2011.